Dr. Hoashoo, M.B. ([Kingston, Jamaica] : Planters' Punch, 1930)
Dr. Hoashoo M.B. (Mrs. Yuen), one of the two lady doctors in Jamaica, [1930].
NLJCols20082021
Keywords: Chinese - Jamaica - History; Chinese - Jamaica; Physicians - Jamaica